Correlation between Quick of Blood and Intradialytic Hypertension on Chronic Kidney Disease Stage V Patients in dr. Soebandi Jember Hospital - Novail Alif Muharrom; Suryono Suryono; Cicih Komariah (Faculty of Medicine, University of Jember, 2018)
Intradialytic hypertension is one of the complications of chronic kidney disease patients (CKD) stadium V undergoing routine hemodialysis. There is still no definite data on incidence of intradialytic hypertension in Indonesia. Therefore, it is important to do further research about the relationship between factors of intraialytic hypertension with incident intradialytic hypertension as preventionefforts morbidity and mortality in patients CKD stadium V undergo hemodialysis. One of the factors is quick of blood (QB). The purpose of this research is to know the connection between QB with intradialytic hypertension on patients PGK stadium V at RSD dr. Soebandi Jember. This research is a type of observational analytic study with cross sectional method which is implemented in the dialysis unit at RSD dr. Soebandi Jember in October 2017. Population and sample in this research are all patients who undergo PGK stadium V routine hemodialysis in RSD dr. Soebandi Jember at a number of 82samples. The data obtained were tested normalitasnya with the Kolmogorov-Smirnov test with the results of the significance of 0.71, indicating the data is distributed normally. Pearson test generates the value of significance (p) 0.032 and strong relationship (r) 0.237 indicating that there is a meaningful relationship with the powerful relationship between weak QB with the incidence of hypertension in patients intradialisis CKD stadium V at RSD dr. Soebandi Jember. Keywords: CKD, intradialytic hypertension, quick of blood